Effects of a Mentor Program for Coaches on the Coach-Athlete Relationship - Jan Arvid Haugan; Frode Moen; Maja Olsen Østerås; Frode Stenseng (MDPI AG, 2021)
The present study was designed to explore the effects of a one-year coach education program on coaches' perceptions of their communication skills and co-orientation of their coach-athlete relationships. The study was designed with an experimental group and a control group. The experiment group consisted of 66 coaches (and 295 athletes) who received formal mentoring and the control group consisted of 41 coaches (and 148 athletes) who did not receive any mentoring. Data were analysed using structural equation modelling with autoregressive cross-lagged analysis. Results from the self-reported questionnaire at pre-test and post-test showed that the reciprocity of the coach-athlete relationships was not statistically significant. However, coaches' experience of change in attention skills from the pre-test to the post-test positively predicted changes in their own perception of the coach-athlete relationship, whereas this association was not significant in the athletes' perceptions. Moreover, the coach education programme increased coaches' perception of their relational bonds with their athletes, but this increase did not correspond with an increase in athletes' perception of the relational bonds with their coach. Practical implications and suggestions for further research are discussed in light of these findings.